Changes in the Fungal Marker β-D-Glucan After Antiretroviral Therapy and Association With Adiposity. (11th November 2019) - Dirajlal-Fargo, Sahera; Moser, Carlee; Rodriguez, Katherine; El-Kamari, Vanessa; Funderburg, Nicholas T; Bowman, Emily; Brown, Todd T; Hunt, Peter W; Currier, Judith; McComsey, Grace A
Abstract: Background: Bacterial translocation in HIV is associated with inflammation and metabolic complications; few data exist on the role of fungal translocation. Methods: A5260s was a substudy of A5257, a prospective open label randomized trial in which treatment-naïve people with HIV (PWH) were randomized to tenofovir-emtricitabine (TDF/FTC) plus atazanavir-ritonavir (ATV/r), darunavir-ritonavir (DRV/r), or raltegravir (RAL) over 96 weeks. Baseline was assessed, and changes in β-D-glucan (BDG) were assessed at weeks 4, 24, and 96. Wilcoxon rank-sum tests were used to compare distribution shifts in the changes from baseline between treatment arms and linear regression models to assess associations between BDG and measures of inflammation, body composition, and insulin resistance. Results: Two hundred thirty-one participants were randomized; 90% were male, the median age was 36 years, HIV-1 RNA was 4.56 log10c/mL, and CD4 cell count was 338 cells/mm 3 . There was an overall increase in BDG over 96 weeks (1.57 mean fold-change; 95% confidence interval, 1.39 to 1.77) with no differences between arms. Twofold higher BDG levels at week 96 were associated with increases in trunk fat (8%) and total fat (7%) over 96 weeks ( P ≤ .035). At week 4, BDG correlated with I-FABP, a marker of enterocyte damage, and zonulin, a marker of intestinal permeability ( r = .19–.20; P < .01). Conclusions: In treatment-naïve participants initiating antiretroviral therapy (ART) with TDF/FTC and either RAL or ATV/r, DRV/r, BDG, a marker of fungal translocation, increased similarly in all arms over 96 weeks. This may represent continued intestinal damage during ART and resulting fungal translocation. Higher BDG was associated with larger fat gains on ART.